“You Know, We Live in Fear”: Transit Migrants with Their Neglected Disabilities in Istanbul-Kumkapı - Çakırer Özservet, Yasemin (My University, 2014)
When migrants are not able to reach their target country, they stop by in other countries on their migration route. Kumkapı area is one of the passing points for Europe targeted migration, which is home to long periods of waiting. This study will talk about the obstacles the international migrants go through in Kumkapı-İstanbul region; the immigrants who have left their home and try to keep their culture alive in a place they do not belong to. The obstacles these transit immigrants experience in an urban environment without the facility of making use of public and other services are reviewed with the ethnography method. Kumkapı area has been a transforming area since 1970's, and currently has a social mosaic that is filled with illegality and poverty. This region, which can be called an area of the excluded, has become an area that never gets visited by the other classes of the society.
Keywords: Transit migration; İstanbul; Kumkapı; Neglected Disabilities; Living in a fear